Identifying regional drivers of future land-based biodiversity footprints. (July 2021) - Marquardt, Sandra G.; Doelman, Jonathan C.; Daioglou, Vassilis; Tabeau, Andrzej; Schipper, Aafke M.; Sim, Sarah; Kulak, Michal; Steinmann, Zoran J.N.; Stehfest, Elke; Wilting, Harry C.; Huijbregts, Mark A.J.
Graphical abstract: Highlights: We quantified future land-based biodiversity footprints for three global scenarios. Most continents exceed the planetary boundary in the 'regional rivalry' scenario. North America exceeds the planetary boundary in the 'sustainability' scenario. Reductions in per capita footprints may accompany increases in total footprints. Animal-based consumption remains the largest contributor to future footprints. Abstract: Biodiversity footprints quantify the impacts on ecosystems caused by final consumption in a region, accounting for imports and exports. Up to now, footprint analyses have typically been applied to analyze past or present consumption patterns. Here, we quantify future land-based biodiversity footprints associated with three diverging Shared Socio-economic Pathways (SSPs), using loss in Biodiversity Intactness Index (BII) as an indicator of biodiversity loss. For each SSP, we retrieved socio-economic and land use projections to 2100 from the IMAGE-MAGNET model and calculated associated biodiversity footprints for seven aggregated world regions. We then compared these with the functional diversity component of the biosphere integrity planetary boundary. Our results indicate that the global land-based biodiversity impact stays below the boundary (tentatively set at 90% of original BII) in all scenario-year combinations. Contrastingly, the per capita boundary is transgressed in one, four and five out of the seven world regions in 2100 for SSP1 ('sustainability'), SSP2 ('middle of the road') and SSP3 ('regional rivalry'), respectively. These results indicate a strong difference in the biodiversity impact of final consumption between the regions and between SSPs. Even in the 'sustainability' scenario, the per capita biodiversity footprint of consumption in North America needs to be reduced to meet the per capita boundary. Thus, policy-making to safeguard the environment would benefit from adopting region-specific strategies: focusing on realizing agricultural efficiency gains in regions with unexploited potential, while focusing on promoting dietary changes towards less animal-based consumption in regions with limited potential for additional efficiency gains.